Analisis beban dan tingkat pencemaran di Perairan Dumai, Provinsi Riau - Fitri Ariani; Hefni Effendi; Suprihatin Suprihatin (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
Dumai is an area that has various anthropogenic activities that can result in pressure on the ecosystem in Dumai waters and can cause unproductive waters and decrease biodiversity. This study aims to determine the level of pollution load in Dumai waters using a purposive sampling method. The results of this study indicate that the highest level of pollution is around the Pangkalan Sesai and Purnama areas where the Dumai River flows. The pollution index indicates that the quality status of Dumai waters has been moderately polluted.